Co-parenting Based on Local Wisdom of Toraja Tribe - Yonan Thadius (Universitas Syiah Kuala, 2023)
This study aims to find out the rich treasures of Toraja culture on local parenting that helps Toraja parents in parenting rooted in tongkonan. This study uses descriptive qualitative method through literature study as a tool to obtain data. This study focuses on the perspective of positive parenting, particularly co-parenting rooted in the local wisdom of the Toraja tribe as the research subject. The local wisdom approach is chosen, especially regarding the symbolization, meaning and significance of tongkonan which is part of the cultural identity of the Toraja tribe. In this study, researchers will conduct data collection through observation and interviews as well as literature review to deeply understand the uniqueness of co-parenting in Torajan tribal families, especially in the context of childcare. This study found that co-parenting of Torajan parents in childcare are imbued with cognatic or bilateral (parental) affinity that emphasizes the equality of men and women. This perspective of equality is inherent in the meaning of tongkonan itself, which is to sit together and becomes thick with the presence of matrifocal and patrifocal elements in parenting symbolized through the tongkonan house with alang sura'. Torajan people consider tongkonan house as a symbol of motherhood, while alang sura' (rice barn) as a symbol of father. The tongkonan house and alang sura' also face each other, as they are considered as husband and wife. The meaning of the symbolization refers to mothers and fathers who have equal responsibilities despite playing different roles, where childcare is not solely the domestication of the mother but the father as well.